Perfluorooctane sulfonate (PFOS) removal with Pd-0/nFe(0) nanoparticles: Adsorption or aqueous Fe-complexation, not transformation? - Park, S (2018)
This work was funded by the Strategic Environmental Research and Development Program (ER-2426) and Cienciactiva, an initiative of CONCYTEC (grant contract number 276-2015-FONDECYT). We also wish to acknowledge Gnanasiri S. Premachandra and Chloe De Perre for their analytical chemistry support.